Superalloys 2004 (Tenth International Symposium) 2004
DOI: 10.7449/2004/superalloys_2004_917_924
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Vacuum Arc Remelting of Alloy 718 Ingots

Abstract: Vacuum Arc Remelting (VAR) is typically the final melting process in the production of a wide range of alloys including superalloys, titanium, zirconium and specialty steels. During this process, a DC arc is struck under vacuum between a consumable electrode and a water-cooled copper crucible. The heat from the arc melts the electrode and molten metal droplets from the electrode solidify in the crucible to form an ingot. The purpose of VAR is to cast a sound, segregation free ingot. The soundness of the final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…(To permit a more thorough assessment of the impact of neglecting mass flux and solidification, results (not shown here) from a CFX simulation including both buoyancy and Lorentz forces predicted maximum surface velocities of approximately 0.8 cm/s, which is in reasonable agreement with the results of transient axisymmetric simulations from other authors, which did include mass flux and solidification. [3,5] However, it should be noted that other authors' work predicts significant upflow velocity near the pool center, whereas the CFX simulations carried out in this work predict the majority of the upflow at closer to midradius. )…”
Section: Liquid Metal Pool Behaviormentioning
confidence: 76%
See 1 more Smart Citation
“…(To permit a more thorough assessment of the impact of neglecting mass flux and solidification, results (not shown here) from a CFX simulation including both buoyancy and Lorentz forces predicted maximum surface velocities of approximately 0.8 cm/s, which is in reasonable agreement with the results of transient axisymmetric simulations from other authors, which did include mass flux and solidification. [3,5] However, it should be noted that other authors' work predicts significant upflow velocity near the pool center, whereas the CFX simulations carried out in this work predict the majority of the upflow at closer to midradius. )…”
Section: Liquid Metal Pool Behaviormentioning
confidence: 76%
“…Previous modeling of the pool behavior (assuming that the arc distribution was axisymmetrical) [3][4][5] has indicated that, under the usual melting conditions for 508-mm-diameter nickel superalloy ingots, the pool was mostly controlled by the buoyancy force. However, analysis of the arc behavior during an experimental melt of a 440-mm INCONEL* 718 electrode into a 508-mm ingot under nominally diffuse conditions suggested that, most of the time, the electrical center of the arc was located at a radial distance of around 100 mm from the ingot centerline and, superimposed upon the normal high-speed random motion typical of diffuse arc VAR, rotated in a time-averaged sense clockwise or counterclockwise around the ingot centerline with a period of approximately 20 to 40 seconds.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulations corroborate the foundry practice knowledge that abrupt variations on the controlling parameters of VAR induce perturbations in the temperature and composition of the interdendritic liquid that should have a strong influence on freckle nucleation and growth. [22][23][24] Nevertheless, no direct simulation of freckles in VAR for industrial application has been accomplished, mostly because of insufficient high-temperature physical properties data needed and excessive computational requirements of the transient multiphysics, multiscale threedimensional models.…”
Section: Density Inversionmentioning
confidence: 99%
“…The pool flow of the VAR ingot is caused by a competition between the Lorentz force and buoyancy force. The buoyancy force is dominant for low-current VAR-ingots (e.g., Ni-base superalloys [9]), whereas the Lorenz force is dominant for the high-current VAR ingot (e.g., Ti-base alloys).…”
Section: B Multia Simulation Of the Var-ingotmentioning
confidence: 99%